Film Dokumenter Sebagai Sarana Dialog Antar Agama - Simatupang, Bona Ventro (Sekolah Tinggi Diakones HKBP, 2025)
This research shows how films can influence someone's way of life. Documentaries, as a storytelling medium, are complex agents of change, embedded in real communities, real lives, and real stories. Because documentaries relate directly to the human social world, watching them involves complex cognitive, psychological, emotional, social and political processes. Therefore, documentaries are a powerful medium for stimulating discussion, reflection and behavior change. This article explores the power of visual narrative and positive media representation as a form of interreligious para social relational dialogue. This article also dives into its practical applications while providing best practices that filmmakers can use to harness this power, as well as reviewing the literature on the social, cognitive, and neurobiological impacts that documentaries may have. This interdisciplinary theory of cognitive-sociological change places documentary films as a tool for increasing interreligious competence because of their unique ability to convey visual stories with interesting characters, thereby creating humanizing experiences and reflectively changing perceptions.